2016
DOI: 10.1016/j.diagmicrobio.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolites as potential diagnostic and prognostic biomarkers for acute community acquired pneumonia

Abstract: Early diagnosis of acute community-acquired pneumonia (CAP) is important in patient triage and treatment decisions. To identify biomarkers that distinguish patients with CAP from non-CAP controls, we conducted an untargeted global metabolome analysis for plasma samples from 142 patients with CAP (CAP cases) and 97 without CAP (non-CAP controls). Thirteen lipid metabolites could discriminate between CAP cases and non-CAP controls with area-under-the-receiver-operating-characteristic curve of >0.8 (P ≤ 10(-9)). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 48 publications
3
46
1
Order By: Relevance
“…30 Pneumonia was defined by radiological evidence of new or increased pulmonary infiltrate in a chest radiograph and at least one of the following symptoms (cough with or without sputum production, dyspnea, tachypnea, or pleuritic chest pain) plus one auscultatory finding or one sign of infection (core body temperature 438°C, shivers, leukocyte count 410 000 cells/μL or o4000 cells/μL) as described previously. 31 Routine respiratory virus testing in the clinical microbiology laboratory NPA samples were collected in viral transport medium (VTM) as described previously. 32 Routine testing for respiratory viruses was performed using antigen detection by DFA (D 3 Ultra 8 DFA Respiratory Virus Screening and Identification Kit, Diagnostic Hybrids, Inc., Quidel, San Diego, CA, USA), which included influenza A virus, and influenza B virus, parainfluenza viruses 1-3, respiratory syncytial virus (RSV), human metapneumovirus (hMPV) and adenovirus.…”
Section: Data Collectionmentioning
confidence: 99%
“…30 Pneumonia was defined by radiological evidence of new or increased pulmonary infiltrate in a chest radiograph and at least one of the following symptoms (cough with or without sputum production, dyspnea, tachypnea, or pleuritic chest pain) plus one auscultatory finding or one sign of infection (core body temperature 438°C, shivers, leukocyte count 410 000 cells/μL or o4000 cells/μL) as described previously. 31 Routine respiratory virus testing in the clinical microbiology laboratory NPA samples were collected in viral transport medium (VTM) as described previously. 32 Routine testing for respiratory viruses was performed using antigen detection by DFA (D 3 Ultra 8 DFA Respiratory Virus Screening and Identification Kit, Diagnostic Hybrids, Inc., Quidel, San Diego, CA, USA), which included influenza A virus, and influenza B virus, parainfluenza viruses 1-3, respiratory syncytial virus (RSV), human metapneumovirus (hMPV) and adenovirus.…”
Section: Data Collectionmentioning
confidence: 99%
“…Groups have found metabolic patterns specific to sepsis, some metabolites that potentially can identify severe versus less severe pneumonia, and certain metabolites that may predict poorer outcomes. For instance, To's group found that 13 lipid metabolites could discriminate between CAP and non-CAP cases with an AUC of >0.8, and that trihexosylceramide levels were higher in fatal cases [103]. A separate group used 1D 1H nuclear magnetic resonance (NMR) spectra to generate metabolic profiles from 15 patients with pneumonia; comparing the metabolic profiles using Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) they were able to differentiate cases of VAP from those without [104].…”
Section: Metabolomics and Lipidomicsmentioning
confidence: 99%
“…Cancer represented the largest category, with 14 studies 11,12,25,29,[31][32][33][34][35][36][37][38][39] ; cardiovascular 28 , rheumatologic 26 , ‡ , renal ‡ , and respiratory 16 diseases were represented by only one or two studies. Other health states with a small to medium number of studies included neuro/neuropsychiatric 18,19 , endocrine 21,24,40,41 , and infectious disease 14,15,27,30,42,43 , as well as a general 'other' category 17,[44][45][46] .…”
Section: Biofluid-based Metabolomics Studies Cover Many Health Statesmentioning
confidence: 99%